Semi-wild horse grazing as a rewilding strategy: assessing effects on vegetation structure and composition in the Côa Valley, Portugal - Ribeiro, Inês; Aliácar, Sara; Domingos, Tiago; McCracken, Davy; Proença, Vânia (Frontiers in Ecology and Evolution, 2025)
Mediterranean landscapes are characterized by fine-grained land-cover mosaics of interspersed vegetation types and high wildfire vulnerability, where grazing plays a key role in regulating vegetation structure and composition. This study explores the early effects, over a three-year period, of a transition from extensive commercial cattle grazing to semi-wild horse grazing in two rewilding areas in the Côa Valley region, Portugal. Using grazing exclusion areas as control, we test whether the less intensive regime of semi-wild horse grazing can be used to manage vegetation structure and composition, to mitigate local fire hazard and promote biodiversity. The monitoring scheme followed a paired design, where each survey site of 40 m × 40 m comprises four sampling plots of 10 m × 10 m, including two fenced plots (grazing exclusion) and two plots open to grazing. Effects on vegetation structure were assessed considering grass height, shrub height, shrub cover and aboveground biomass, as well as effects on plant species richness, turnover, and forbs-to-grasses ratio (F:G ratio) and the community-level importance of grasses and forbs. Results showed that grass height had a greater increase in ungrazed plots, suggesting that semi-wild horse grazing helps limit grass height. There were no significant differences in shrub metrics between treatments (i.e. horse grazing vs. no grazing), indicating that horse grazing did not effectively control woody vegetation. While species richness remained stable, species temporal turnover was higher in ungrazed plots. Additionally, the F:G ratio and the importance value of forbs were higher under horse grazing, suggesting potential benefits for anthophilous insects. These findings indicate that semi-wild horse grazing contributes to maintaining open habitats by controlling grass dominance, thereby reducing local fire hazard and potentially fostering habitat and food resources for insects. While this demonstrates the potential of using semi-wild horse grazing in rewilding, the results also suggest that horses alone, particularly at low densities, have limited impact on woody vegetation structure.